Desenvolvimento de metodologia baseada em dois estágios para a produção de tomate e pimentão amarelo em pó - Jorge, Aline (2018)
Powdered dehydrated products are widely consumed by food industries of ready and pre-ready to eat products, due to its facility of transportation, storage and extended shelf life. It is desirable that these products can maintain its characteristics as closer as possible from fresh fruit when they are rehydrated and should bring economics advantages for the industry. The general objective of this work consists in producing a multi-stage drying system for fruits and vegetables for maintaining its characteristics and nutritional benefits, with lower processing costs. For this, it was necessary to develop and test a prototype of the drying system, hermetically closed for allowing the processing under low pressure and temperature and hot air flow. The research was developed in the steps of literature revision, raw materials choice, definition of drying parameters, obtaining and characterization of the tomato and sweet pepper powders. A decision-making tool was applied for the choice of the most proper drying method. In tomato were evaluated the contents of ascorbic acid, total phenolic compounds, β-carotene, lycopene, fructose, glucose, citric acid, 5-hydroxy-methyl-2-furfural (HMF) and tissue changes. In yellow sweet bell pepper were evaluated the contents of glucose, fructose, sucrose, HMF, protein, fibers, color, browning indices and the carotenoid profile identification. According to the results of the tomato powder evaluation, the drying process in two stages lead to lower losses of sugars, high contents of carotenoids, total phenolic compounds, HMF formation, surface hardening. In the evaluated treatments of processing of yellow sweet bell pepper, the drying process in two stages resulted in losses of ascorbic acid content, sugars, increase of browning indices. For the choice of drying process, several aspects were considered, since different parameters may imply in different acquisition costs, energy consumption, and the quality effects of the final product, in this context the drying process in hot air flow was pointed as advantageous for tomato drying.